CARACTERIZAÇÃO GEOMORFOLÓGICA DO PARQUE ESTADUAL DO VALE DO CODÓ, JAGUARIAÍVA – PR: SUBSÍDIOS AO PLANO DE MANEJO - Crist, Pedro (2017)
The essay on screen versifies about the geomorphology of Vale do Codó State Park, located in Jaguariaíva-Pr municipality. This unit of conservation was created by means of state decree in the year of 2007. Although it have past some years since its creation, it hasn‟t actually implemented because it does not count with advisory council, plan of handling and physical structure. The general objective of the research provided in the geomorphologic characterization of the studying area, emphasizing geomorphologic features with potential to develop imprint pedagogical activities, ecotourism, leisure and nature contemplation. The methodological approaches used were the Geosystemic Theory of integrated manner considering the physical, biological and anthropic aspects. The methodological procedure involved literature revision, analysis of topographic map, geologic and morphological and fieldwork to identification in loco of the geomorphologic features, obtaining UTMS`s coordinates and photographic register realization. How results, stand out several micro and meso features geomorphologic sculped by rainwaters on the sandstone of the Formação Furnas, such as dissolution basin, the wells, the ruiniform reliefs, the flutings, the limpest and features originated by erosive processes associated from waters in the kettles and waterfall. Also are notables the macro features like canyons of Jaguariaíva river, Lajeado Grande and the Escarpa Devoniana.